UBI – the Cornerstone of a New Social Deal (Journal of Universal Excellence, 2026)
Research Question (RQ): How would it be best to introduce UBI (Universal Basic Income) in Slovenia and the EU?Purpose: This article analyses the possibility of UBI introduction in Slovenia and the EU based on eighteen years of observation of the flourishing UBI ‘eco-system’ developed in Slovenia and in the EU that reached little to no success. The longstanding efforts for UBI implementation brought some disturbing and frustrating results in time of COVID. The academics, advocates, and experts will have to start a new circle of research on UBI implementation. In the 21st century, the UBI could prove to be the most important, basic, cornerstone of a New Social Deal consisting of three UTD pillars: a pillar of universal basic rights, a free market/trade pillar, and a pillar of democratic social institutions. UTD Social Deal could help Slovenia to secure its position as the core EU member state and could prevent the EU from disintegration in current emergency-over-emergency times. The aim of the paper is also to identify the obstacles and mistakes made within Slovenian UBI discourse in order not to repeat the history.Method: Eighteen years of research with the participant observation method and international comparative analyses using the “circle of social innovation – circle of hope” as the analytical tool.Results: The research proved that UBI is not possible to introduce in Slovenia or in the EU in the manner proposed 12 years ago. The approach has to be re-adjusted, and proposal updated. Organization: The academics, advocates, and experts will have to start a new circle of research on UBI implementation hopefully learning from previous endeavours.Society: The new concept of UTD could be the basis of a new social agreement that could prevent the disintegration of the EU.Originality: The topic of UBI is still under researched in Slovenia and such in detail historical overview and comparison between the countries is of essential value to conduct further argued discussion about the mentioned topic.Limitations/Further research: UBI would have a tremendous impact on the de-bureaucratization of the state. Therefore, the research on UBI is limited on every and each step of current state funding and should be therefore in the future conducted only within non-state research entities.
Keywords: UBI; UTD; three-pillar system; new social deal